Therapeutic Options for the Treatment of Coronavirus Disease (COVID-19). Issue 4 (October 2020) - Snawerdt, Jessica; Finoli, Lauren; Bremmer, Derek N.; Cheema, Tariq; Bhanot, Nitin
Abstract : Coronavirus disease 2019 (COVID-19) has resulted in an unprecedented pandemic, challenging practitioners to identify safe and effective therapeutic options in a limited amount of time. The rapid genomic sequencing of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) provided a significant number of therapeutic targets. Repurposed and investigational agents are being studied for use in COVID-19. Although knowledge is rapidly expanding in regard to COVID-19 and there is promise with a few agents, there are no definitely proven effective therapies at this time. Supportive care remains the mainstay of therapy while ongoing clinical trials are being conducted.